ISOLATION OF β-SITOSTEROL AND LUPENONE FROM THE METHANOL ROOT EXTRACT OF Cassia sieberiana DC (Fabaceae) - IBRAHIM, J. S.; MUHAMMAD, S.; ATIKU, I.; ABDULLAHI, S.M.; ILYAS, M.; ISYAKA, M. S.; SANI, Y.M, (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2020)
Cassia sieberiana DC (Fabaceae) is a small tree with wide spread in India and tropical Africa. The plant is used ethnomedicinally in African for the treatment of malaria, inflammations and other infectious diseases. Some of the pharmacological activities of the plant include antispasmodic, anti-inflammatory and antimicrobial activities.β-sitosterol and lupenone were isolated by a combination of column chromatography and gel filtration of ethylacetate fraction of the methanol root extract of the plant. The structures of the compounds were determined by analysis of their UV, IR, 1D and 2D NMR spectra as well as comparison with the literature data. This is the first report for the isolation of these compounds from the plant. Keywords: